Knowledge-based integrated production management model - Muniz, Jorge [UNESP]; Batista Junior, Edgard Dias [UNESP]; Loureiro, Geilson (Emerald Group Publishing Limited, 2010)
Purpose - This paper aims to propose a model of production management that integrates knowledge management, as a third dimension, to the production and work dimensions and to identify factors that promote a favorable context for knowledge sharing and results achievement in the production operations shop floor environment.Design/methodology/approach - The model proposed is built from opportunities identified in the literature review.Findings - The factors in the model integrate its three main components: knowledge management, production organization and work organization, providing a representation of the dynamics of the workplace and shop floor environment.Practical implications - The proposed model and its factors allow managers to better understand and to improve the organization activities, because it integrates knowledge management with the production organization and work organization components of traditional models.Originality/value - Literature acknowledges the role of knowledge as competitive advantage, but it is still dealt in an implicit way within the traditional models of production management. This paper proposes a model and factors that provide a favorable context for tacit knowledge sharing and results achievement in the production operations shop floor environment. The model explicitly integrates knowledge management with traditional models' components.
Keywords: Production management; Knowledge management; Knowledge sharing; Modelling